Designing Material Learning for 5th Grade Elementary School using Science, Technology, Engineering, and Mathematics (STEM) - Tyas Heruprahoro; Subuh Anggoro; Ristiana Dyah Purwandari (UM Purwokerto Press, 2023)
This type of research uses research and development (R&D). This research aims to produce teaching materials based on Science, Technology, Engineering, And Mathematics (STEM) and determine the feasibility of teaching materials. This teaching material is created and developed to improve critical thinking skills on the theme of events in the lives of elementary school students on the material properties nature of things. Research and development in the field of education uses the ADDIE model. Technique data analysis was carried out quantitatively and qualitatively. Data collection instruments in the form of tests and notes. Assessment of teaching materials based on Science, Technology, Engineering, And Mathematics (STEM) according to the assessment of material experts and practitioners is feasible to use. Use of teaching-based materials STEM is feasible to improve critical thinking skills on the theme of events in the participant's life elementary school students on the material properties of objects. STEM- based teaching materials can not only be used in the research subject, but can be used as a source of learning and reference for schools. STEM- based teaching materials present material that is developmentally appropriate science and technology. The use of STEM- based teaching materials encourages educators to utilize technology to achieve understanding of thematic concepts to improve students' critical thinking skills to the maximum according to learning objectives.